THE EFFECT OF COMPETENCE AND DISCIPLINE OF WORK ON PUBLIC SATISFACTION IN THE REGIONAL OFFICE OF THE MINISTRY OF RELIGION IN WEST SUMATERA PROVINCE WITH QUALITY OF SERVICE AS AN INTERVENING VARIABLE - Ermayenti, Ermayenti; Heryanto, Heryanto (Archives of Business Research, 2019)
The study aims to explain the presence or absence of the influence of competence and discipline in the Staffing Section of the Regional Office of the Ministry of Religion of West Sumatra Province and measure the influence of competence and discipline on the Regional Office of the Ministry of Religion of West Sumatra Province. This research was conducted from August to October 2018 in the Regional Office of the Ministry of Religion, West Sumatra Province. The sample used in this study was 70 respondents using sampling sampling method. The independent variables in this study are competence (X1) and discipline (X2). The dependent variable is satisfaction (Y). And the intervening variable of service (I). Technical data collection is a questionnaire. The data analysis technique uses descriptive analysis. To determine the effect of independent variables on the dependent variable partially, t test is used, while to determine the independent effect of the dependent variable simultaneously, F. test is used. The assumption used in the validity test is if Rcount > Rtable items are declared valid. Rcount shown in the table above, from each item shows that Rcount > Rtable item is declared valid. Based on the validity of the competency instrument (X1), work discipline (X2), Satisfaction (Y) and service (I) all items are declared valid and the reliability test results indicate that the instrument has high reliability and meets the criteria of valid and reliable instrument requirements. Based on the results of the study that the independent variable of competence (X1) and discipline (X2) has a significant effect on satisfaction (Y) through service (I) as an intervening variable.